Impact of resident involvement in endoscopic bladder cancer surgery on pathological outcomes. (3rd May 2016) - Bos, Derek; Allard, Christopher B.; Dason, Shawn; Ruzhynsky, Vladimir; Kapoor, Anil; Shayegan, Bobby
Abstract: Objective : Transurethral resection of bladder tumor (TURBT) pathology specimens which lack muscle are associated with clinical upstaging and may necessitate repeat resections, potentially delaying curative treatment. This study evaluated whether resident involvement in TURBT is associated with suboptimal perioperative outcomes.Materials and methods : All TURBTs performed at a Canadian healthcare institution from November 2011 to June 2014 were reviewed. Multivariable logistic regression models assessed associations between intraoperative resident involvement and TURBT muscle presence. Among high-risk patients (high grade, ≥ T1 or carcinoma in situ ) who underwent cystectomy, time from TURBT to cystectomy was compared between resident and attending urologists with the log-rank test.Results : In total, 463 TURBTs were identified. In multivariable analyses, residents were less likely to obtain muscle in specimens for all TURBTs [adjusted odds ratio (aOR) 0.59, p = 0.03] and the subset of 275 high-risk TURBTs (aOR 0.41, p = 0.006). Among patients who underwent cystectomy, time to cystectomy was delayed by a median of 23 days when residents were involved in the initial high-risk TURBT compared with attending urologists only ( p = 0.024).Conclusions : In this single academic center series, intraoperative resident involvement was associated with a decreased rate of muscle presence in TURBT specimens and a prolonged time to cystectomy.